(untitled) (Journal of Foreign Language Studies, 2023)
The diversity and complexity of Italian clitic pronouns cause many difficulties for Vietnamese students of Italian, whose native language does not have this grammatical category. The data analysis of 721 written assignments by 309 students at the Department of Italian Studies, Hanoi University, reveals that there are universal as well as unique features in the students’ acquisition of Italian clitic pronouns due to their mother tongue transfer. On that basis, this study offers some recommendations for more effective teaching content and methodology.